Clinical Impact of Viral Load on the Development of Hepatocellular Carcinoma and Liver-Related Mortality in Patients with Hepatitis C Virus Infection - Ran Noh; Doo Hyuck Lee; Byoung Woon Kwon; Yong Hyun Kim; Suk Bae Kim; Il Han Song (Gastroenterology Research and Practice)
Aim. This study aimed to assess clinical impact of hepatitis C viral load on the development of hepatocellular carcinoma (HCC) and liver-related mortality in HCV-infected patients. Methods. A total of 111 subjects with chronic HCV infection who were available for serum quantitation of HCV RNA were recruited in this retrospective cohort. Cox-proportional hazards models were used to calculate hazard ratio (HR) of developing HCC and liver-related mortality according to serum HCV RNA titers. Results. HCC was developed in 14 patients during follow-up period. The cumulative risk of HCC development was higher in subjects with high HCV RNA titer (log HCV RNA IU/mL > 6) than subjects with low titer (log HCV RNA IU/mL ≦ 6) (HR = 4.63, P=0.032), giving an incidence rate of 474.1 and 111.5 per 10,000 person-years, respectively. Old age (HR = 9.71, P=0.014), accompanying cirrhosis (HR = 19.34, P=0.004), and low platelet count (HR = 13.97, P=0.009) were other independent risk factors for the development of HCC. Liver-related death occurred in 7 patients. Accompanying cirrhosis (HR = 6.13, P=0.012) and low albumin level (HR = 9.17, P=0.002), but not HCV RNA titer, were significant risk factors related to liver-related mortality. Conclusion. Serum HCV RNA titer may be considered an independent risk factor for the development of HCC but not liver-related mortality.